Validation of the problematic social casino gaming scale. Issue 3 (1st September 2020) - Li, Wen; Mills, Devin; Nower, Lia
ABSTRACT: Few investigations have focused on problematic social casino gaming. Social casino games are a type of video game that feature gambling elements. Unlike gambling machines, social casino games present with a number of added interactive features that render them more like video games. Therefore, problematic social casino gaming may present with symptoms that reflect both problem video gaming and problem gambling. To investigate the overlap, this study examined a new measure – the Problematic Social Casino Gaming Scale (PSCGS) – in 436 social casino game players. Exploratory factor analysis revealed a single-factor structure that was further supported by confirmatory factor analysis. The PSCGS demonstrated high internal consistency. The latent profile analysis of the PSCGS classified participants into three groups, representing different levels of problematic social casino gaming. Players classified as high severity played social casino games more frequently, were more likely to spend money on social casino games, and evidenced greater severity of problem video gaming and problem gambling than other players. Collectively, results provide initial evidence of the psychometric properties of the PSCGS and characteristics of problematic social casino gaming. Such findings could inform future research into the etiology, nature, and course of problematic social casino gaming.